UMA Anaulacomera SINGULAR DO ESTADO DE MINAS GERAIS (ORTHOPTERA: PHANEROPTERIDAE) - Piza Jr, S. de Toledo (REVISTA DE AGRICULTURA, 2016)
UMA Anaulacomera SINGULAR DO ESTADO DE MINAS GERAIS (ORTHOPTERA: PHANEROPTERIDAE)